I'm having a difficult time figuring out some of these! For some reason the -1 in this problem is throwing me off - I think! Here's what I came up with last time, I keep getting a different answer each time I work it.
3/(y+5) -1 = (4-y)/(2y+10)
3/(y+5)-1 = (4-y)/2(y+5)
y is not equal to -5
LCD is 2(y+5)
2(y+5)*3/(y+5) = 6
2(y+5)*-1 = -2(-y-5)
6+2y+10 = (4-y)
Can you help me figure out where I am going wrong?
Ok, we have:
3/(y+ 5)- 1= (4- y)/(2y+ 10), so if we take the common denom. of the left hand side we will ...
Rational expressions are solved. The solution is detailed and well presented. The response received a rating of "5" from the student who originally posted the question.